The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/pros.23944
|View full text |Cite
|
Sign up to set email alerts
|

Ascleposide, a natural cardenolide, induces anticancer signaling in human castration‐resistant prostatic cancer through Na+/K+‐ATPase internalization and tubulin acetylation

Abstract: Background: Cardiac glycosides, which inhibit Na + /K + -ATPase, display inotropic effects for the treatment of congestive heart failure and cardiac arrhythmia. Recent studies have suggested signaling downstream of Na + /K + -ATPase action in the regulation of cell proliferation and apoptosis and have revealed the anticancer activity of cardiac glycosides. The study aims to characterize the anticancer potential of ascleposide, a natural cardenolide, and to uncover its primary target and underlying mechanism ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Among such potential repurposed drug candidates belong, for example, cardiac glycosides (CGs), currently used in clinical practice for the treatment of heart diseases, such as congestive heart failure or cardiac arrhythmias. Furthermore, CGs also exert very promising anticancer activity both in vitro and in vivo [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], which is based mainly on the induction of complex signaling cascades in Na + /K + -ATPase (NKA) signalosome and induction of immune response. This fact could be utilized not only for cancer treatment but also in the treatment of a plethora of autoimmune and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Among such potential repurposed drug candidates belong, for example, cardiac glycosides (CGs), currently used in clinical practice for the treatment of heart diseases, such as congestive heart failure or cardiac arrhythmias. Furthermore, CGs also exert very promising anticancer activity both in vitro and in vivo [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], which is based mainly on the induction of complex signaling cascades in Na + /K + -ATPase (NKA) signalosome and induction of immune response. This fact could be utilized not only for cancer treatment but also in the treatment of a plethora of autoimmune and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…e KEGG analyses showed that most of the enriched biological information was associated with the thyroid cancer pathway, small-cell lung cancer pathway, prostate cancer pathway, bladder cancer pathway, and other cancer pathways. According to an analysis of the literature, we found that multiple target proteins contained in these pathways can activate the MAPK signalling pathway [38][39][40][41]. erefore, we speculated that Rhizoma Curcumae may regulate the proliferation of nasopharyngeal carcinoma cells by regulating the MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ascleposide, a natural cardiac steroid lactone isolated from Saussurea lappa , has been found to inhibit DU145 prostate cancer cell growth 149 . Ascleposide downregulates the expression of cyclin D1, cyclin A, and CDK4 in a dose-dependent manner, and also downregulaets c-Myc (an early identified oncogenes) in human prostate cancer cells 150 . C-myc indirectly regulates the cell cycle through the dissociation of the CDK repressor protein p21 from the CDK4/6-cyclin D complex 151 .…”
Section: Mitosis-associated Kinasesmentioning
confidence: 99%
“…C-myc indirectly regulates the cell cycle through the dissociation of the CDK repressor protein p21 from the CDK4/6-cyclin D complex 151 . Therefore, ascleposide exerts indirect and direct effects on cell cycle regulation, and decreases the G1 distribution of cells while increasing the proportion of cells in G2/M and sub-G1 phase 150 . The p21 and p27 Cip/Kip proteins are crucial CDK-interacting protein/kinase inhibitory proteins in mitotis 152 .…”
Section: Mitosis-associated Kinasesmentioning
confidence: 99%